Pembuatan Sistem Informasi Manajemen Klinik dengan Rekam Medis: Studi Kasus di Klinik Kebon Arum Boyolali - Yanuar Wisnu Triaji; Rinta Kridalukmana; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2017)
The manual process of registration, inspection, payment, reporting and administrative employees at a clinic is not efficient. An information system to assist and facilitate a user in the process of a medical record is needed. The purpose of this research is to design and build a management information system for a clinic, specifically for Kebon Arum Clinic at Boyolali. The method used in this system development is the waterfall, which consists of the plan requirements, process design, and implementation. This application is built using PHP language, CodeIgniter framework, and MySQL database. As the results, the application can solve problems on manual clinic registration, queues, services, payments and patient data.